An anencephalic monocephalus diprosopus "headed twin": postmortem and CT findings with emphasis on the cranial bones - Ekinci, Gazanfer; Balci, Sevim; Erzen, Canan (The Turkish Journal of Pediatrics, 2005)
Monocephalus diprosopus is a form of conjoined twinning characterized by a single body, one unusual head and two faces or a spectrum of duplication of the craniofacial structures. Such cases have been mainly described according to postmortem pathologic examination. This presented case is a 26-week-stillborn female fetus, with unusual facial appearance with four eyes, two mouths, two noses, two ears and a defective cranial vault. To our knowledge, a detailed computerized tomography (CT) examination of the aberrant facial and cranial bones of such a case has not been reported to date. In this reported case, we present an anencephalic monocephalus diprosopus "headed twin", and describe the CT findings with emphasis on the cranial bones.